Toward cleaner production: Can mobile phone technology help reduce inorganic fertilizer application? Evidence using a national level dataset - Nawab Khan; Ram L. Ray; Hazem S. Kassem; Muhammad Ihtisham Abdullah; Simplice Asongu; Stephen Ansah; Shemei Zhang (African Governance and Development Institute (AGDI), 2021)
Increasing agricultural production and optimizing inorganic fertilizer (IF) use are imperative for agricultural and environmental sustainability. Mobile phone usage (MPU) has the potential to reduce IF application while ensuring environmental and agricultural sustainability goals. The main objectives of this study were to assess MPU, mobile phone promotion policy, and whether the mediation role of human capital can help reduce IF use. This study used baseline regression analysis and propensity score matching, difference-in-differences (PSM-DID) to assess the impact of MPU on IF usage. However, the two-stage instrumental variables method (IVM) was used to study the effects of mobile phone promotion policy on IF usage. This study used a national dataset from 7,987 rural households in Afghanistan to investigate the impacts of MPU and associated promotion policies on IF application. The baseline regression outcomes showed that the MPU significantly reduced IF usage. The evaluation mechanism revealed that mobile phones help reduce IF application by improving the human capital of farmers. Besides, evidence from the DID technique showed that mobile phone promotion policies lowered IF application. These results remained robust after applying the PSM-DID method and two-stage IVM to control endogenous decisions of rural households. This study results imply that enhancing the accessibility of wideband in remote areas, promoting MPU, and increasing investment in information communication technologies (ICTs) infrastructure can help decrease the IF application in agriculture. Thus, the government should invest in remote areas to facilitate access to ICTs, such as having a telephone and access to a cellular and internet network to provide an environment and facility to apply IF effectively. Further, particular policy support must focus on how vulnerable populations access the internet and mobile phone technologies.
Keywords: 330; mobile phone usage; propensity score matching; difference-in-difference; inorganic fertilizer usage; human capital; sustainable development; Afghanistan